2016
DOI: 10.1097/scs.0000000000002342
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Soft Tissue Airway Volume Analysis in Mandibular Distraction

Abstract: Three-dimensional computed tomography has been used in both preoperative planning of mandibular distraction osteogenesis and in the evaluation of postoperative resolution of tongue-based airway obstruction. The authors present a case report using software to predict postdistraction airway volume during virtual surgical planning (VSP) of mandibular distraction osteogenesis in a 7 year old. The predicted increase in airway volume derived from VSP was 33.57% (1716 mm(3) preoperatively to 2292 mm(3) postvirtual di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Virtual surgical planning was utilized preoperatively using the 3-D-reformatted CT data. Mandibular distraction end point was based on predicted skeletal advancement of the mandible and airway volume after the virtual surgery (Mhlaba et al, 2016). Standard protocol for all patients included a latency period of 24 hours followed by distractor activation at 1 to 1.5 mm/d (0.5 mm twice daily [BID] or 1 mm am /0.5 mm pm ) for 2 to 5 days followed by 1 mm/d (0.5 mm BID) until the virtual distraction end point was reached.…”
Section: Methodsmentioning
confidence: 99%
“…Virtual surgical planning was utilized preoperatively using the 3-D-reformatted CT data. Mandibular distraction end point was based on predicted skeletal advancement of the mandible and airway volume after the virtual surgery (Mhlaba et al, 2016). Standard protocol for all patients included a latency period of 24 hours followed by distractor activation at 1 to 1.5 mm/d (0.5 mm twice daily [BID] or 1 mm am /0.5 mm pm ) for 2 to 5 days followed by 1 mm/d (0.5 mm BID) until the virtual distraction end point was reached.…”
Section: Methodsmentioning
confidence: 99%
“…25 3D reconstructions are obtained and volumetric analysis of the upper airway is performed and frequently used in preoperative planning. 14,16,26 Previous studies have demonstrated that mandibular distraction is effective in expanding the upper airway. 10,[27][28][29] However, predicting how much expansion is necessary to affect a physiologic response is challenging, 16 and an arbitrary percentage of volume increase is often used to determine the approximate length of mandibular advancement.…”
Section: Discussionmentioning
confidence: 99%
“…Second, an understated feature of VSP is the ability to simulate soft tissue changes that occur from virtual surgery, including external soft-tissue elements such as facial contours and airway simulation. 51 52 Though some limitations in VSP software exist in terms of soft-tissue modeling, the ability to compare simulated and postoperative airway volumes and external soft tissue drape can be used as a modicum of quality control.…”
Section: Anatomic and Technical Considerationsmentioning
confidence: 99%